2011
DOI: 10.1038/nn.2847
|View full text |Cite
|
Sign up to set email alerts
|

High-fat feeding promotes obesity via insulin receptor/PI3K-dependent inhibition of SF-1 VMH neurons

Abstract: SF-1-expressing neurons of the ventromedial hypothalamus (VMH) control energy homeostasis, but the role of insulin action in these cells remains undefined. We show that insulin activates PI3-kinase (PI3k) signaling in SF-1 neurons and reduces firing frequency in these cells via activation of KATP-channels. These effects are abrogated in mice with insulin receptor (IR) deficiency restricted to SF-1 neurons (SF-1ΔIR-mice). While body weight and glucose homeostasis remain unaltered in SF-1ΔIR-mice under normal ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
238
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(253 citation statements)
references
References 52 publications
(74 reference statements)
13
238
0
2
Order By: Relevance
“…23 In addition, we find ARL13B localization within the primary cilia of hypothalamic neurons, especially in the ventromedial nucleus of the hypothalamus, which is considered as a crucial site of regulation of energy homeostasis. [24][25][26][27] Finally, consistent with this finding, recent evidence in ciliopathies has linked obesity to the regulation of homeostasis within the hypothalamus. 28 Our zebrafish and MEF experiments indicate that the Y86C missense variant identified in this study is hypomorphic, as overexpression of Y86C cDNA is not efficient in rescuing the arl13b sco zebrafish and Arl13b hnn MEF phenotypes.…”
Section: Discussionsupporting
confidence: 76%
“…23 In addition, we find ARL13B localization within the primary cilia of hypothalamic neurons, especially in the ventromedial nucleus of the hypothalamus, which is considered as a crucial site of regulation of energy homeostasis. [24][25][26][27] Finally, consistent with this finding, recent evidence in ciliopathies has linked obesity to the regulation of homeostasis within the hypothalamus. 28 Our zebrafish and MEF experiments indicate that the Y86C missense variant identified in this study is hypomorphic, as overexpression of Y86C cDNA is not efficient in rescuing the arl13b sco zebrafish and Arl13b hnn MEF phenotypes.…”
Section: Discussionsupporting
confidence: 76%
“…For example, subsets of proopiomelanocortin (POMC) and steroidogenesis factor 1 (SF1) neurons are responsive to either leptin or insulin (15)(16)(17)(18)(19), and, therefore, it is not entirely known if the phenotype of mice with PI3K deletion in those neurons is due to lack of leptin or insulin signaling. Conditional deletion of PI3Kα or PI3Kβ in POMC and SF1…”
Section: Introductionmentioning
confidence: 99%
“…Among these neurons, several studies have shown that the steroidogenic factor 1 (SF1) expressing ones, which are restricted to the hypothalamic ventromedial nucleus (VMN), are important modulators of metabolic functions through their ability to detect variations of extracellular concentrations of glucose, insulin, leptin, and orexin to coordinate insulin/glucose homeostasis (1)(2)(3)(4)(5). The SF1 transcription factor itself is a key actor of energy homeostasis ,as SF1 knockout (KO) mice are obese (6).…”
mentioning
confidence: 99%